LIP5, a MVB biogenesis regulator, is required for rice growth - Wang, Mengxue; Luo, Shuwei; Fan, Baofang; Zhu, Cheng; Chen, Zhixiang (Frontiers in Plant Science, 2023)
LYST-INTERACTING PROTEIN5 (LIP5) is a conserved regulator of multivesicular body (MVB) biogenesis in eukaryotes. In Arabidopsis, AtLIP5 is a target of stress-responsive MITOGEN-ACTIVATED PROTEIN KINASE3 and 6 and mediates stress-induced MVB biogenesis to promote stress responses. However, Arabidopsis atlip5 knockout mutants are normal in growth and development. Here we report that rice OsLIP5 gene could fully restore both the disease resistance and salt tolerance of the Arabidopsis oslip5 mutant plants to the wild-type levels. Unlike Arabidopsis atlip5 mutants, rice oslip5 mutants were severely stunted, developed necrotic lesions and all died before flowering. Unlike in Arabidopsis, LIP5 regulated endocytosis under both stress and normal conditions in rice. These findings indicate that there is strong evolutionary divergence among different plants in the role of the conserved LIP5-regulated MVB pathway in normal plant growth.